Constructing Organizational Identities on the Web: A Case Study of Royal Dutch/Shell* - Coupland, Christine; Brown, Andrew D. (Journal of Management Studies, 2004)
abstract In this paper we analyse two of the e‐mail exchanges that had been posted on Royal Dutch/Shell's Web site in order to investigate how organizational identities are constructed through processes of description, questioning, contestation and defence. Organizational identities may be regarded as ongoing arguments between insiders and between ostensible insiders and outsiders, who deploy various persuasive techniques in their efforts to render hegemonic their versions of an organization's identity. Making plausible through persuasive rhetoric is a complex task, and requires a discourse analytic methodology and an analytical focus on whole utterances, in order to explicate how identity‐as‐argument is enacted. The research implications of our paper are twofold. First, by focusing on language as an opaque phenomenon, taken‐for‐granted ways of being persuasive are made strange and hence more visible. Second, our understanding of organizations as situated in ongoing, multi‐focused arguments, illustrates a new way of conceptualizing the polyphonic, genre‐relevant nature of institutional identities.